2004
DOI: 10.1007/s00213-004-2052-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of the pedunculopontine tegmental nucleus in sensorimotor gating and reward-related behavior in rats

Abstract: These findings suggest that GABAergic neurotransmission in the PPTg plays an important role for sensorimotor gating at intermediate ISIs and for response selection under demanding schedules of reinforcement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…Interestingly, it was recently shown that PPTg-targeting GABAergic neurons in the LGP are activated at both prepulse and prepulse + pulse (PPI) conditions, and that transient inactivation of this region by lidocaine decreases PPI in mice. Furthermore, infusions of both GABA A and GABA B receptor antagonists into the PPTg decrease PPI, suggesting that the LGP regulates PPI by acting on GABA receptors in the PPTg (Diederich and Koch, 2005;Takahashi et al, 2007). Thus, it is possible that systemic (but not prefrontal) injections of baclofen used in this study, affects PPTg in the opposite direction, thereby causing an increase in basal PPI.…”
Section: Regional Effects Of Baclofenmentioning
confidence: 86%
“…Interestingly, it was recently shown that PPTg-targeting GABAergic neurons in the LGP are activated at both prepulse and prepulse + pulse (PPI) conditions, and that transient inactivation of this region by lidocaine decreases PPI in mice. Furthermore, infusions of both GABA A and GABA B receptor antagonists into the PPTg decrease PPI, suggesting that the LGP regulates PPI by acting on GABA receptors in the PPTg (Diederich and Koch, 2005;Takahashi et al, 2007). Thus, it is possible that systemic (but not prefrontal) injections of baclofen used in this study, affects PPTg in the opposite direction, thereby causing an increase in basal PPI.…”
Section: Regional Effects Of Baclofenmentioning
confidence: 86%
“…3B). This is interesting, since a previous study using pharmacological inactivation of the pedunculopontine tegmental nucleus (PPN) shows that the reduction of PPI after blocking neurotransmission in this nucleus is more pronounced at ISIs of 100 and 520 ms than at 25 and 1020 ms (Diederich and Koch 2004). Since the PPN is a key element of the cortico-limbic striatopallidotegmental circuit that mediates and regulates PPI Fendt et al 2001) it was concluded that PPI after very short and very long ISIs might recruit different brain circuits.…”
Section: Discussionmentioning
confidence: 97%
“…The acoustic activation could either result from the distinct hissing tone caused by the air puffs leaving the Teflon tubes or from the primary visual activation via crossmodal activation through the somatosensory stimulus [Diederich and Koch, 2005;Lugo et al, 2008;McDowell et al, 2006;Senkowski et al, 2008;Diederich and Colonius, 2008].…”
Section: Discussionmentioning
confidence: 99%